Entrance dynamics of CH4 molecules through a methane-water interface - Murina, Ezequiel Luis (2015)
We studied the entrance mechanism of methane molecules into bulk water by Molecular Dynamics simulation over a broad time window. We corroborated that the presence of absorbed methane, under the studied thermodynamic state (298 K and roughly 10 MPa), does not influence the molecular configuration of water interface. Some representative interfacial trajectories were analyzed in detail and we propose an entrance mechanism in which interfacial water is not actively involved in the dissolution process. Finally, we described the Helmholtz Free Energy profile through the interface and obtained the dissolution free energy of methane in water.